Implementasi Akad Mudharabah pada Usaha Mikro di Desa Lakapera Kabupaten Buton Tengah (International Forum of Researchers and Lecturers, 2023)
The implementation of the mudharabah contract among micro-enterprises in Lakapera Village, Buton Tengah Regency, demonstrates significant potential in improving the community's economic well-being. This study aims to analyze the community’s understanding of the mudharabah contract, its practical application, and the challenges faced. Using a qualitative approach, data were collected through in-depth interviews and observation. The results indicate that despite existing challenges, the positive impact of mudharabah implementation is significant for the growth of micro-enterprises.